Development Strategy for Rabbit in Soppeng Regency - S. N. Sirajuddin; S. Nurlaelah; R. Abriati (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
The purpose of this research was to formulate alternative strategy that can be applied in developing rabbit farming in Soppeng Regency. The research was carried out from January 2011 to February 2011 in Lalabata Sub District, Soppeng Regency. The experiment was a descriptive study in which samples were taken purposively. Experimental data were analysed using SWOT analysis. The result research indicated that some strategies that might be developed, including 1) to extent market segment for rabbit ,2) to develop excellence breeding of rabbit 3) to intensify the extension regarding nutritive value of rabbit meat and a better management for rabbit farming.